Liquid component for electrolytic capacitor and electrolytic capacitor
By using specific liquid components and conductive polymers in the electrolytic capacitor, the problem of degradation of the performance of the electrolytic capacitor at high temperatures is solved, the heat resistance and stability are improved, and the service life of the electrolytic capacitor is extended.
Patent Information
- Application Number
- CN202080084806.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-09
- Filing Date
- 2020-12-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-12-08
AI Technical Summary
The performance of existing electrolytic capacitors deteriorates at high temperatures, especially due to the low thermal stability of phthalates and the deterioration of conductive polymers when the pH rises, resulting in increased ripple current, heating and performance reduction.
Using a liquid component containing a central atom (such as boron, aluminum, silicon) and a ligand, the ligand bonds multiple coordination atoms to the central atom, and forms a dielectric layer between the anode body and the cathode body with a dielectric layer in the electrolytic capacitor. The configuration is to use conductive polymers and liquid components to control the pH of the liquid components and the concentration of complex anions to improve stability.
The heat resistance and stability of the electrolytic capacitor are significantly improved, the deterioration of conductive polymers and the pH rise are suppressed, and the service life of the electrolytic capacitor is extended.
Smart Images

Figure CN114830274B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a liquid component for an electrolytic capacitor and an electrolytic capacitor including the liquid component. Background Art
[0002] In an electrolytic capacitor having a liquid component such as an electrolyte, the liquid component functions as a de facto cathode material. Various studies have been conducted on the composition of the liquid component.
[0003] For example, Patent Document 1 describes the use of an electrolyte solution containing a salt of phthalic acid or borodisalicylic acid and an amine compound in an electrolytic capacitor. In addition, Patent Document 2 teaches an electrolytic capacitor containing a conductive polymer and a conductive auxiliary liquid. The conductive auxiliary liquid contains an organic solvent having a boiling point of 150° C. or higher and an aromatic compound having at least one hydroxyl group.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 11-67604
[0007] Patent Document 2: International Publication No. 2013 / 94462 Pamphlet Summary of the invention
[0008] Problem that the invention aims to solve
[0009] In recent years, it is expected that the allowable ripple current of electrolytic capacitors will be increased. If the ripple current increases, the heat generated by the electrolytic capacitor increases, and the temperature of the electrolytic capacitor tends to rise. The salts of phthalic acid and borodisalicylic acid described in Patent Document 1 have low thermal stability, so if an electrolyte containing such salts is used, the performance of the electrolytic capacitor is sometimes reduced. In addition, the conductive auxiliary liquid of Patent Document 2 has a tendency to increase the pH if the temperature of the electrolytic capacitor increases. If the pH increases, the conductive polymer deteriorates and the performance of the electrolytic capacitor decreases.
[0010] Solutions for solving problems
[0011] In view of the above, one aspect of the present application relates to a liquid component for an electrolytic capacitor, which comprises a central atom and a ligand, wherein the central atom is at least one selected from boron, aluminum and silicon, and the ligand has a plurality of coordinating atoms bonded to the central atom, and the coordinating atoms are at least one selected from oxygen and nitrogen, and are bonded to a carbon atom that does not have an oxo group.
[0012] Another aspect of the present application relates to an electrolytic capacitor including: an anode body having a dielectric layer formed on a surface thereof; a cathode body; and a conductive polymer and the above-mentioned liquid component disposed between the anode body and the cathode body.
[0013] Still another aspect of the present application relates to an electrolytic capacitor including: an anode body having a dielectric layer formed on a surface thereof; a cathode body; and the above-mentioned liquid component disposed between the anode body and the cathode body.
[0014] Effects of the Invention
[0015] According to the above aspects of the present application, it is possible to provide an electrolytic capacitor and a liquid component for an electrolytic capacitor having excellent heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present application.
[0017] Figure 2 It is a schematic diagram for explaining the structure of the capacitor element according to the embodiment. DETAILED DESCRIPTION
[0018] While the novel features of the present invention are described in the appended claims, the present invention both as to structure and content, together with other objects and features of the present invention, will be better understood from the following detailed description taken in conjunction with the accompanying drawings.
[0019] The electrolytic capacitor according to the present application includes an anode body having a dielectric layer formed on the surface thereof, a cathode body, and a liquid component disposed between the anode body and the cathode body.
[0020] The liquid component includes: a central atom selected from at least one of boron, aluminum, and silicon; and a ligand having a plurality of coordination atoms bonded to the central atom. In other words, the ligand has a plurality of coordination atoms bonded to the central atom.
[0021] The coordinating atom is at least one selected from an oxygen atom and a nitrogen atom, and is bonded to a carbon atom having no oxo group (=O). When the coordinating atom is an oxygen atom, the oxygen atom does not form a carboxyl group or a carboxyl anion.
[0022] More specifically, the oxygen atom as the coordinating atom may be an alcoholic or phenolic hydroxyl group, alkoxy oxygen, or oxy group. Among them, from the viewpoint of stable bonding to the central atom, it is preferred that the alcoholic or phenolic alkoxy oxygen is bonded to the central atom.
[0023] On the other hand, when the coordinating atom is a nitrogen atom, the nitrogen atom is a nitrogen atom that forms an amino group, an amide group, an imide group, an imide anion, or the like.
[0024] The coordination compound is composed of a central metal and a ligand. The coordination compound includes a complex and a complex salt. The ligand is not particularly limited and can form a complex anion together with the central atom. That is, the coordination compound can be a complex anion. For the coordination compound, an organic molecule having a plurality of coordination atoms (in other words, a coordination organic compound) coordinates with the central metal to form a coordination compound (the first coordination compound). That is, the first coordination compound has a ligand derived from such an organic molecule (coordinating organic compound). The ligand can take a structure in which a hydrogen atom, a hydroxyl group, an amino group or an imino group bonded to a coordination atom is separated from the organic molecule.
[0025] The ligand preferably contains an electron-withdrawing substituent. Such a substituent easily stabilizes the electrons of the coordinating atoms of the ligand, so that the product during hydrolysis is not easy to corrode the electrodes of the capacitor. Here, as the electron-withdrawing substituent, a nitro group, a carboxyl group, an ester group, a halogen atom (fluorine atom, chlorine atom, etc.), an acyl group, a tosyl group, a keto group, a cyano group, a methylsulfonyl group, etc. can be cited.
[0026] On the other hand, the ligand may include a substituent with electron donating property. Such a substituent easily causes electrons to flow into the empty orbit on the central atom and stabilize, and therefore particularly helps to increase the stability of the liquid component in a high humidity environment when water is added. Here, as the substituent with electron donating property, amino, alkyl, aryl (phenyl, etc.), alkoxy, etc. may be mentioned.
[0027] The ligand may be derived from, for example, a polyol having an aromatic ring and at least a first hydroxyl group and a group containing a second hydroxyl group. That is, the above-mentioned organic molecule (coordinating organic compound) may be a polyol. The ligand derived from a polyol refers to a residue after removing hydrogen atoms and / or hydroxyl groups from the polyol, and / or the polyol. The first hydroxyl group may be bonded to the aromatic ring. The group containing the second hydroxyl group may be bonded to the ortho position of the first hydroxyl group of the aromatic ring. The group containing the second hydroxyl group may be the second hydroxyl group or an alkyl group having the second hydroxyl group. As an alkyl group having the second hydroxyl group, for example, an alkyl group having 1 to 4 carbon atoms may be mentioned. As an alkyl group having the second hydroxyl group, for example, a hydroxymethyl group, a hydroxyethyl group, a hydroxypropyl group, or a hydroxybutyl group may be mentioned. From the viewpoint of the stability of the complex anion, a hydroxymethyl group is preferred.
[0028] More preferably, the organic molecule may be a compound represented by the following general formula (1), (2), (3), (4), (5) or (6).
[0029] [Chemical formula 1]
[0030]
[0031] [Chemical formula 2]
[0032]
[0033] [R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Each independently represents a hydrogen atom, a halogen atom, a hydroxyl group, an alkoxy group having 1 to 10 carbon atoms, a carboxyl group, a group having 2 to 10 carbon atoms having an ester bond, a saturated aliphatic hydrocarbon group having 1 to 24 carbon atoms which may have a substituent, an unsaturated aliphatic hydrocarbon group having 2 to 24 carbon atoms which may have a substituent, or an aromatic hydrocarbon group having 6 to 14 carbon atoms which may have a substituent.]
[0034] Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.
[0035] Examples of the alkoxy group having 1 to 10 carbon atoms include methoxy, ethoxy, n-propoxy or isopropoxy, n-butoxy, sec-butoxy, isobutoxy or tert-butoxy, n-pentyloxy, n-hexyloxy, octyloxy, decyloxy and phenoxy.
[0036] Examples of the group having 2 to 10 carbon atoms having an ester bond include alkoxycarbonyl groups having 2 to 10 carbon atoms. Examples of the alkoxycarbonyl group include groups in which the hydrogen atom of a carboxyl group is substituted with a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a pentyl group, an octyl group or a nonyl group.
[0037] Examples of the saturated aliphatic hydrocarbon group having 1 to 24 carbon atoms which may have a substituent include an alkyl group having 1 to 24 carbon atoms and a cycloalkyl group having 3 to 24 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2-ethylpropyl group, an n-hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 4-methylpentyl group, a 1-ethylbutyl group, a 2-ethylbutyl group, a 1-propylpropyl group, a 2-propylpropyl group, a 1-isopropylpropyl group, a 2-isopropylpropyl group, an n-heptyl group, a 1-methylhexyl group, a 2-methylhexyl group, a 3-methylhexyl group, a 4-methylhexyl group, a 5-methylhexyl group, a 1-ethylpentyl group, a 2-ethylpentyl group, a 3-ethylpentyl group, a 2,2-dimethylpropyl group, a 1-propyl The alkyl group may be 1-20, 1-16, 1-12, 1-2-butylbutyl, 1-isobutylbutyl, 2-isobutylbutyl, 1-tert-butylbutyl, 2-tert-butylbutyl, 1,1,3,3-tetramethylbutyl, nonyl, and decyl. The alkyl group may have 1 to 20, 1 to 16, or 1 to 12 carbon atoms. Examples of the cycloalkyl group include cyclopentyl, cyclohexyl, cyclopentyl, and cyclooctyl. The cycloalkyl group may have 5 to 10 carbon atoms, or 5 to 8 carbon atoms.
[0038] Examples of the unsaturated aliphatic hydrocarbon group having 2 to 24 carbon atoms which may have a substituent include alkenyl. Examples of the alkenyl group include vinyl, propenyl, butenyl, pentenyl, hexenyl, octenyl, decenyl, isopropenyl, etc. The unsaturated aliphatic hydrocarbon group may have 2 to 18 carbon atoms.
[0039] Examples of the substituent that the saturated aliphatic hydrocarbon group having 1 to 24 carbon atoms or the unsaturated aliphatic hydrocarbon group having 2 to 24 carbon atoms may optionally have include a hydroxyl group, an alkoxy group (such as an alkoxy group having 1 to 4 carbon atoms), a carboxyl group, a nitro group, a halogen atom, a cyano group, and an amino group.
[0040] As the aromatic hydrocarbon group having 6 to 14 carbon atoms which may optionally have a substituent, an aryl group, an arylalkyl group (or an aralkyl group) and the like can be mentioned. As the aryl group, a phenyl group, a tolyl group, a xylyl group, a naphthyl group and the like can be mentioned. The aryl group can be a group having an aromatic hydrocarbon ring having 6 to 10 carbon atoms. As the arylalkyl group, for example, an alkyl group having 1 to 4 carbon atoms which has an aryl group having 6 to 10 carbon atoms can be mentioned. As the arylalkyl group, for example, a benzyl group and a phenethyl group can be mentioned. As the substituent group, for example, an alkyl group (such as an alkyl group having 1 to 6 carbon atoms), a hydroxyl group, an alkoxy group (such as an alkoxy group having 1 to 4 carbon atoms), a carboxyl group, a nitro group, a halogen atom, a cyano group, an amino group and the like can be mentioned.
[0041] More specifically, examples of the polyol having a second hydroxyl group bonded to an aromatic ring include catechol, pyrogallol, gallic acid, gallic acid esters (gallic acid alkyl esters (esters with alkyl groups having 1 to 4 carbon atoms, etc.), hexahydroxybenzene, 1,2-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 4,4'-(2,3-dimethyltetramethylene) dipyrocatechol, 2,3,4,4'-tetrahydroxydiphenylmethane, etc. Substituents may be bonded to the aromatic rings of these polyols.
[0042] Typical examples of the polyol having a first hydroxyl group and an alkyl group (hydroxymethyl or the like) containing a second hydroxyl group include salicyl alcohol, 2,5-dihydroxybenzyl alcohol, 2,6-bis(hydroxymethyl)-p-cresol, etc. Substituents may be bonded to the aromatic rings of these polyols.
[0043] As the substituent that the aromatic ring of the polyol may have, for example, there can be mentioned the following: 1 ~R 6 The groups or atoms described herein (however, excluding hydrogen atoms).
[0044] The number of molecules of the polyol coordinated by each central atom can be 1 molecule, or more than 2 molecules. From the viewpoint of the stability of the complex anion, a polyol such as a polyol having more than 2 molecules (e.g., 2 molecules or 3 molecules) coordinated by each 2 central atoms can be selected. It should be noted that the number of molecules is equivalent to the number of ligands coordinated by each central atom.
[0045] When the central atom is boron or aluminum, for example, a tetracoordinated complex anion can be formed. Typically, a complex anion formed by dehydrating two molecules of diol and coordinating with a boron atom or an aluminum atom (typically, boron dicatechol, etc.) can be cited. In addition, when the central atom is silicon, for example, a pentacoordinated or hexacoordinated complex anion can be formed. Typically, a complex anion formed by dehydrating three molecules of diol and coordinating with a silicon atom can be cited.
[0046] From the viewpoint of reducing the ESR of the electrolytic capacitor, the electrolytic capacitor preferably further comprises a conductive polymer disposed between the anode body and the cathode body. The conductive polymer is, for example, a π-conjugated conductive polymer, which is usually doped with a dopant to improve conductivity. It is believed that by making the liquid component contain the first coordination compound (complex anion, etc.), dedoping of the dopant is suppressed, thereby suppressing degradation of the conductive polymer or reduction of conductivity.
[0047] The pH of the liquid component is preferably 6 or less, more preferably 4 or less, and still more preferably 3.8 or less or 3.6 or less. By setting the pH of the liquid component to 4 or less, deterioration of the conductive polymer is further significantly suppressed.
[0048] The first coordination compound (complex anion, etc.) is acidic and thus can contribute to controlling the pH within the above range. However, the liquid component may further contain an acid component.
[0049] The concentration of the complex anion included in the liquid composition can, for example, exceed 0.1 mass %, or can be more than 1.0 mass %. By including the complex anion in this way, the stability of the liquid composition at high temperatures is greatly improved, and the heat resistance of the electrolytic capacitor is also significantly improved. Wherein, from the viewpoint of appropriately maintaining the viscosity of the liquid composition, the content of the complex anion included in the liquid composition can, for example, be below 30 mass %, or can be below 20 mass %.
[0050] Here, the concentration of complex anion is defined as: the maximum amount of complex anion that the central atom included in the liquid component and the part with a plurality of coordinated atoms with said structure can form.Here, no matter in fact whether to form complex anion, all assume that the central atom and part all form complex ion to calculate maximum amount.Wherein, in the case where the equivalent of the central atom is different from the equivalent of part, the above-mentioned maximum amount certainly calculates with the equivalent of less one party.
[0051] The quantitative and qualitative analysis of the complex anion can be performed, for example, by the following method.
[0052] <Qualitative Analysis>
[0053] First, weigh 30mL of liquid component in a glass container with airtight lid, and utilize the infrared absorption spectrum (IR) of the liquid component in the container to measure the measurement device (IRSprit [Shimadzu Corporation (strain) system]) of regulation. Next, the container that houses the liquid component is airtight, and is kept for a certain time under a high temperature environment. Thereafter, the liquid component in the container is cooled and IR is measured again. The stability of the complex anion can be evaluated by the change of the stretching vibration spectrum of the bond between the central atom-coordinating atom. It can be said that the smaller the spectrum change, the higher the stability of the complex anion.
[0054] <Quantitative Analysis>
[0055] First, weigh 30mL of liquid component in the glass container with airtight lid, utilize the nuclear magnetic resonance spectrum (NMR) of the liquid component in the measuring device (AVANCE III HD [BRUKER system]) of regulation to measure the container, obtain the generation ratio (G0) of initial complex anion according to peak intensity.Next, the container that will be accommodated with liquid component is airtight, keeps certain time under hot environment.Thereafter, measure NMR again after the liquid component in the container is cooled, obtain the generation ratio (G1) of complex anion and unreacted organic molecule.Obtain the decomposition rate of complex anion with following formula, can evaluate the stability of complex anion.It can be said that the decomposition rate is smaller, and the stability of complex anion is higher.
[0056] Complex anion generation ratio G1 (%) = (complex anion peak intensity) / (complex anion peak intensity + unreacted organic molecule peak intensity) × 100
[0057] Decomposition rate of complex anions (%) = initial generation ratio of complex anions G0 (%) - generation ratio of complex anions G1 (%)
[0058] The liquid composition may also include at least one selected from the cations comprising nitrogen atoms and the cations comprising phosphorus atoms. It is believed that these cations have, for example, the stability of the complex anion, and improve the dissociation degree of the acid component, the effect of improving the conductivity of the liquid composition. The cation comprising nitrogen atoms may be an ammonium ion of various structures, and the cation comprising phosphorus atoms may be a phosphonium ion. That is, at least one selected from the cations comprising nitrogen atoms and the cations comprising phosphorus atoms may be an onium cation. The content of the onium cation contained in the liquid composition may be, for example, more than 0.1 mass %, or less than 30 mass %.
[0059] As the cation containing a nitrogen atom, at least one selected from secondary ammonium ions, tertiary ammonium ions and quaternary ammonium ions can be cited. As the amine generating the ammonium ion, aliphatic amines, aromatic amines, heterocyclic amines and the like can be used. Among them, aliphatic amines having a molecular weight of 72 to 102 are preferred in terms of high dissociation degree.
[0060] As the amine generating ammonium ions, for example, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, N,N-diisopropylethylamine, tetramethylethylenediamine, hexamethylenediamine, nitrile amine, nitrile amine, adamantane amine, aniline, phenethylamine, toluidine, pyrrolidine, piperidine, piperazine, morpholine, imidazole, pyridine, pyridazine, pyrimidine, pyrazine, 4-dimethylaminopyridine, etc. These may be used alone or in combination of two or more.
[0061] The quaternary ammonium ion may be an ion of an amidine. Examples of amidines that generate ammonium ions include acetamidine, 1-amidinopyrazole, benzamidine, and pyridine-3-carboxamidine. The amidine may have a substituent (e.g., the electron-withdrawing or electron-donating substituents exemplified above).
[0062] The amidine ion also includes imidazolium (i.e., imidazolium ion). As the imidazolium, it is sufficient to be a cation having a 1,3-oxadiazole ring. The imidazolium may have a substituent (electron-withdrawing or electron-donating substituents exemplified above). As the imidazolium, there can be mentioned imidazolium, imidazolium having a substituent (alkyl, aryl, etc.) at at least one of the 1-position and the 3-position. Examples of the imidazolium having a substituent at at least one of the 1-position and the 3-position include 1,3-dimethylimidazolium, 1,3-diisopropylimidazolium, 1,3-dibutylimidazolium, 1,2,3,4-tetramethylimidazolium, 1-methyl-3-propylimidazolium, 1-ethyl-3-methylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-butyl-3-methylimidazolium, and 1-benzyl-3-methylimidazolium.
[0063] In an electrolytic capacitor not containing a conductive polymer (for example, an aluminum electrolytic capacitor), it is preferable that the liquid component contains amidine ions in order to suppress an increase in ESR.
[0064] When the above-mentioned liquid component is kept at a temperature of 145°C for 1000 hours, the increase in pH can be suppressed to less than 3. That is, when the pH before the liquid component is kept at a temperature of 145°C for 1000 hours is set to X, and the pH after being kept at a temperature of 145°C for 1000 hours is set to Y, the difference between Y and X (YX) can be suppressed to less than 3. This means that the stability of the liquid component is high, and it is not easy to increase the pH even at high temperatures (that is, it is not easy to change from acidic to alkaline). It is believed that the above-mentioned ligand is not easy to decompose, and it is not easy to increase the acid component such as carboxylic acid. Therefore, it is not easy to corrode the electrode of the electrolytic capacitor. In addition, it is believed that the above-mentioned ligand also has the effect of stabilizing the carboxylic acid coexisting in the liquid component.
[0065] The change in pH can be specifically measured by the following method.
[0066] First, 30 mL of the liquid component is weighed in a glass container with a sealed lid, and the pH (X) of the liquid component in the container at 25°C is measured using a predetermined measuring device (HM-41X manufactured by DKK-TOA CORPORATION). Next, the container containing the liquid component is sealed and kept in an oven at 145°C for 1000 hours. Thereafter, the temperature of the liquid component in the container is returned to 25°C and the pH (Y) is measured again. The difference between the measured values Y and X is obtained, thereby enabling the change in pH to be evaluated.
[0067] In order to suppress the change (YX) of pH to below 3, make the liquid component contain the first coordination compound (complex anion etc.) of appropriate amount.In addition, when the acid component is contained in the liquid component, it is preferred to suppress the consumption of carboxylic acid.Carboxylic acid is easy to have side reaction (such as esterification reaction) with the solvent contained in the liquid component and the moisture that invades from the outside at high temperature.If the acid component reduces because of the side reaction, there is the tendency that pH rises.According to the above, the content of the carboxylic acid contained in the liquid component is, for example, ideally set to below 5 mass %, more preferably set to below 1 mass %.
[0068] Among carboxylic acids, aromatic carboxylic acids are relatively stable. Among them, aromatic carboxylic acids having at least two carboxyl groups and containing at least one aromatic ring are relatively stable for esterification reactions. From the viewpoint of suppressing the increase in viscosity of the liquid component, aromatic carboxylic acids preferably have one or two aromatic rings (C6 benzene ring and / or C10 naphthalene ring, etc.).
[0069] As the aromatic carboxylic acid, a divalent to tetravalent carboxylic acid with higher stability is preferred, and it is ideal that two or more carboxyl groups are directly bonded to each other at the ortho position of the aromatic ring. Specifically, as the aromatic carboxylic acid, phthalic acid, pyromellitic acid, etc. can be used. Among them, phthalic acid is preferred, and phthalic acid is particularly preferred.
[0070] A second coordination compound (or condensate (complex anion, etc.)) of a carboxylic acid and an inorganic acid (e.g., boric acid, phosphoric acid, etc.) can be used. As the second coordination compound, for example, a coordination compound of a carboxylic acid and boric acid is preferred. As the second coordination compound, specifically, boron disalicylic acid, boron diglycolic acid, boron dioxalic acid, etc. can be used. Such a second coordination compound has a higher thermal stability than carboxylic acid, but is easily decomposed at a high temperature of, for example, 150°C or more.
[0071] The amount of complex anions and cations (electrolyte salts) contained in the liquid component is preferably 0.1% by mass or more and 50% by mass or less, the stability of the liquid component at high temperatures is greatly improved, and the heat resistance of the electrolytic capacitor is also significantly improved. Among them, from the viewpoint of properly maintaining the viscosity of the liquid component, the content of the electrolyte salt contained in the liquid component can be, for example, greater than 1% by mass and less than 30% by mass, or greater than 10% by mass and less than 25% by mass.
[0072] The molar ratio of complex anions to cations (=complex anions / cations) is, for example, 0.5 or more and 2 or less, or 0.8 or more and 1.2 or less, preferably 0.9 or more and 1.1 or less. In this case, the stability of the liquid component at high temperatures is further improved, and the stability of the complex anions and the degree of dissociation of the acid component are further improved, which can further improve the conductivity of the liquid component.
[0073] The ratio of complex anion in electrolyte salt is preferably more than 15 mass % or more than 30 mass %, more preferably more than 50 mass % or more than 60 mass %. In this case, the stability of liquid composition at high temperature can be further improved. The ratio of complex anion in electrolyte salt is below 90 mass %, preferably below 85 mass % or below 80 mass %, more preferably below 75 mass % or below 70 mass %. In this case, the stability of complex anion and the dissociation degree of acid component are further improved, and the conductivity of liquid composition can be further improved. These lower limits and upper limits can be combined arbitrarily.
[0074] The amount of water contained in the liquid component can be more than 0.1 mass % and less than 30 mass %, or more than 0.5 mass % and less than 30 mass %. In this way, even if more water is contained, the first coordination compound (complex anion, etc.) is not easy to hydrolyze, so the pH of the liquid component can be maintained stable. In addition, acid components such as carboxylic acid are not easy to increase, and corrosion of the electrode of the electrolytic capacitor is not easy to occur.
[0075] The liquid component may further contain a solvent. The type of solvent is not particularly limited. From the perspective of improving the heat resistance of the electrolytic capacitor, it is ideal to use at least a polymer polyether solvent. Here, the weight average molecular weight (Mw) of the polymer polyether solvent is, for example, 150 or more. The polymer polyether solvent has high thermal stability and is not prone to side reactions with ligands. Examples of the polymer polyether solvent include polyalkylene glycols such as polyethylene glycol and polypropylene glycol, polyglycerols, and polyethers (for example, ethers obtained by alkylating the ends of polyalkylene glycols and polyglycerols). Since the polymer polyether solvent ideally has the lowest possible viscosity, it is ideal not to contain an aromatic ring with a rigid structure. The weight average molecular weight (Mw) of polyethylene glycol may be, for example, 190 to 400, or 200 to 300.
[0076] In this specification, the weight average molecular weight (Mw) is a value in terms of polystyrene measured by gel permeation chromatography (GPC). In general, GPC is measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as a mobile phase.
[0077] The content of the polymer polyether solvent contained in the liquid component may be, for example, 0.5% by mass or more, 1% by mass or more, and preferably 20% by mass or more. The content of the polymer polyether solvent may be 90% by mass or less.
[0078] As solvents other than the polymer polyether solvent, low molecular weight glycol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, glycerol, etc., can be included. Low molecular weight glycol compounds or glycerol are believed to improve the orientation of the conductive polymer, improve the conductivity, and reduce ESR. Among them, ethylene glycol is preferred in terms of relatively low viscosity, high thermal conductivity, and excellent heat release.
[0079] The content of ethylene glycol contained in the liquid component may be, for example, 3.0% by mass or more, preferably 10% by mass or more. The content of ethylene glycol may be 90% by mass or less.
[0080] The liquid component may further include, for example, sulfone compounds, lactone compounds, carbonate compounds, etc. as solvents. As sulfone compounds, cyclopentane, dimethyl sulfoxide, diethyl sulfoxide, etc. may be used. As lactone compounds, γ-butyrolactone, γ-valerolactone, etc. may be used. As carbonate compounds, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), etc. may be used. Solvents may be used alone or in combination of more than two. From the viewpoint of the synthesis of complex anions, lactone compounds are preferably used.
[0081] The conductive polymer disposed between the anode body and the cathode body can be synthesized by applying a solution containing a monomer, a dopant, and an oxidant to the dielectric layer and performing chemical polymerization or electrolytic polymerization on the spot. Alternatively, a pre-synthesized conductive polymer can be applied to the dielectric layer. In this case, for example, a liquid polymer dispersion containing a conductive polymer and a polymer dopant is infiltrated into the dielectric layer to form a conductive polymer film covering at least a portion of the dielectric layer.
[0082] As conductive polymers, polypyrrole, polythiophene, polyaniline, etc. are preferred. They can be used alone, two or more kinds can be used in combination, or they can be copolymers of two or more monomers. It should be noted that in this specification, polypyrrole, polythiophene, polyaniline, etc. refer to polymers using polypyrrole, polythiophene, polyaniline, etc. as basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyaniline, etc. may also contain their respective derivatives. For example, polythiophene contains poly (3, 4-ethylenedioxythiophene) (PEDOT), etc. The weight average molecular weight of the conductive polymer is not particularly limited, for example, 1000 to 100000.
[0083] From the viewpoint of suppressing the dedoping of the conductive polymer, it is desirable to use a polymer dopant (polymer anion, etc.). It is believed that by making the liquid component contain the first coordination compound (complex anion, etc.), the dedoping of the polymer dopant is suppressed, so the degradation of the conductive polymer or the reduction of the conductivity is suppressed. As a polymer dopant (polymer anion, etc.), anions such as polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly (2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid can be cited. They can be used alone or in combination of two or more. In addition, they can be homopolymers or copolymers of two or more monomers. Among them, polystyrene sulfonic acid (PSS) is preferred. The weight average molecular weight of the polymer dopant is not particularly limited, and from the aspect of easily forming a homogeneous solid electrolyte layer, for example, it is preferably 1000 to 1000000.
[0084] Hereinafter, the present invention will be described in more detail based on the embodiments. However, the following embodiments do not limit the present invention.
[0085] Figure 1 is a schematic cross-sectional view of an electrolytic capacitor according to this embodiment. Figure 2 This is a schematic diagram showing a portion of a capacitor element related to an electrolytic capacitor.
[0086] Figure 1 The electrolytic capacitor shown in the figure comprises: a capacitor element 10, a bottomed case 11 for accommodating the capacitor element 10, a sealing member 12 for blocking the opening of the bottomed case 11, a seat plate 13 covering the sealing member 12, leads 14A and 14B extending from the sealing member 12 and penetrating the seat plate 13, lead terminals 15A and 15B for connecting the leads to electrodes of the capacitor element 10, and a liquid component (not shown). The open end of the bottomed case 11 is crimped to the sealing member 12.
[0087] The capacitor element 10 is composed of Figure 2 The wound body is a semi-finished product of the capacitor element 10, which means that no conductive polymer is arranged between the anode body 21 and the cathode body 22 having a dielectric layer on the surface. The wound body is formed by winding the anode body 21 connected to the lead connector 15A and the cathode body 22 connected to the lead connector 15B through the spacer 23. The outermost periphery of the wound body is fixed by the anti-winding tape 24. It should be noted that Figure 2 The diagram shows a partially unfolded state before the outermost circumference of the wound body is fixed.
[0088] Anode body 21 includes a metal foil with a roughened surface, and a dielectric layer is formed on the roughened surface. A conductive polymer is attached to at least a portion of the surface of the dielectric layer to form capacitor element 10. Capacitor element 10 is accommodated in an outer case together with a liquid component (not shown).
[0089] Hereinafter, an example of a method for manufacturing an electrolytic capacitor will be described.
[0090] (i) Step of Preparing Anode Body 21 and Cathode Body 22 Having Dielectric Layers
[0091] A metal foil made of a valve metal is used as the raw material of the anode body 21 and the cathode body 22. In the case of the anode body 21, the surface of the metal foil is roughened by etching treatment or the like, and a plurality of concave and convex portions are formed on the surface of the metal foil. Next, a dielectric layer is formed on the surface of the roughened metal foil by chemical conversion treatment or the like. The surface of the cathode body 22 may also be roughened as needed.
[0092] (ii) Preparation of wound body
[0093] The anode body 21 and the cathode body 22 are wound with the separator 23 interposed therebetween to produce a wound body. The separator 23 may be a nonwoven fabric mainly composed of synthetic cellulose or the like. A stopper tape 24 is arranged on the outer surface of the cathode body 22 located at the outermost layer of the wound body to fix the end of the cathode body 22. The wound body is further subjected to a chemical conversion treatment as required.
[0094] (iii) Step of Forming Capacitor Element 10
[0095] For example, a liquid polymer dispersion is impregnated into the dielectric layer to form a conductive polymer film covering at least a portion of the dielectric layer. Thus, a capacitor element 10 is obtained in which a conductive polymer is arranged between the anode body 21 and the cathode body 22. The process of imparting a polymer dispersion to the surface of the dielectric layer can be repeated twice or more. Thereafter, the liquid component is impregnated into the capacitor element 10. Thus, an electrolytic capacitor having a conductive polymer and a liquid component is obtained.
[0096] (iv) Step of sealing the capacitor element
[0097] The capacitor element 10 and the liquid component are housed in the bottom case 11 in such a manner that the leads 14A and 14B are located on the opening side of the bottom case 11. Next, the opening of the bottom case 11 is blocked with a sealing member 12 through which each lead passes, and the opening end is riveted to the sealing member 12 for curling. A seat plate 13 is arranged on the curled portion to complete the process. Figure 1 An electrolytic capacitor as shown.
[0098] In the above-mentioned embodiment, a winding-type electrolytic capacitor is described, but the scope of application of the present invention is not limited to the above-mentioned, and it can also be applied to other electrolytic capacitors, such as a chip-type electrolytic capacitor using a metal sintered body as an anode body, and a stacked electrolytic capacitor using a metal plate as an anode body.
[0099] [Example]
[0100] The present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0101] 《Preparation of liquid ingredients》
[0102] The components shown in Table 1 were mixed to prepare liquid components LA1 to LA11 (Examples) and LB1 to LB4 (Comparative Examples).
[0103] [Evaluation 1]
[0104] The pH change caused by heating was measured using the liquid components LA1 to LA11 and LB1 to LB4 in Table 1, respectively. More specifically, 30 mL of the liquid component was weighed into a glass container with a sealed lid, and the pH (X) of the liquid component in the container at 25°C was measured using HM-41X manufactured by DKK-TOA CORPORATION. Next, the container containing the liquid component was sealed and kept in an oven at 145°C for 1000 hours, and then the temperature of the liquid component in the container was restored to 25°C and the pH (Y) was measured again. The difference between the measured values Y and X was calculated to evaluate the change in pH. The results are shown in Table 2.
[0105] Table 1
[0106]
[0107] [Table 2]
[0108] Liquid ingredients pH(×) p H(Y) Y-× LA1 1.3 3.0 1.7 LA2 2.1 4.0 1.9 LA3 2.2 3.7 1.5 LA4 2.1 3.7 1.6 LA5 2.2 4.3 2.1 LA6 4.8 7.2 2.4 LA7 2.3 4.5 2.2 LA8 4.8 7.0 2.2 LA9 2.2 4.3 2.1 LA10 2.1 3.4 1.3 LA1 1 6.1 8.8 2.7 LB1 1.6 4.8 3.2 LB2 2.2 5.6 3.4 LB3 5.3 9.4 4.1 LB4 5.8 9.8 4.0
[0109] 《Manufacturing of electrolytic capacitors CA1 to CA6 and CB1 to CB6》
[0110] A wound electrolytic capacitor (diameter 8.0 mm×L (length) 12.0 mm) having a rated voltage of 100 V and a rated capacitance of 15 μF was produced. A specific method for producing the electrolytic capacitor will be described below.
[0111] (Preparation of anode body)
[0112] An aluminum foil having a thickness of 100 μm was etched to roughen the surface of the aluminum foil. Thereafter, a dielectric layer was formed on the surface of the aluminum foil by chemical conversion treatment. The chemical conversion treatment was performed by immersing the aluminum foil in an ammonium adipate solution and applying a voltage of 180 V thereto. Thereafter, the aluminum foil was cut to prepare an anode body.
[0113] (Preparation of cathode body)
[0114] An aluminum foil having a thickness of 50 μm was subjected to etching to roughen the surface of the aluminum foil, and then the aluminum foil was cut to prepare a cathode body.
[0115] (Production of wound body)
[0116] The anode lead connector and the cathode lead connector are connected to the anode body and the cathode body, and the anode body and the cathode body are wound through the separator while the lead connector is wound. The anode lead and the cathode lead are respectively connected to the ends of each lead connector protruding from the wound body. The prepared wound body is chemically converted again to form a dielectric layer at the cut end of the anode body. Next, the end of the outer surface of the wound body is fixed with a winding stopper to prepare the wound body.
[0117] (Preparation of polymer dispersion)
[0118] 3,4-ethylenedioxythiophene and polystyrene sulfonic acid (PSS, weight average molecular weight 100,000) as a polymer dopant are dissolved in ion exchange water to prepare a mixed solution. Iron (III) sulfate (oxidant) dissolved in ion exchange water is added while stirring the mixed solution to carry out a polymerization reaction. After the reaction, the obtained reaction solution is dialyzed to remove unreacted monomers and excess oxidant, thereby obtaining a polymer dispersion containing polyethylene dioxythiophene (PEDOT / PSS) doped with about 5% by mass of PSS.
[0119] (Formation of Solid Electrolyte Layer)
[0120] In a reduced pressure atmosphere (40 kPa), the wound body is immersed in a polymer dispersion contained in a predetermined container for 5 minutes, and then the wound body is lifted from the polymer dispersion. Next, the wound body impregnated with the polymer dispersion is dried in a drying oven at 150° C. for 20 minutes to form a solid electrolyte layer including a conductive polymer layer covering at least a portion of the dielectric layer.
[0121] (Preparation of liquid component)
[0122] The components shown in Table 3 were mixed to prepare liquid components LA1, LA2, LA12 to LA15 (Examples) and LB1 to LB4 (Comparative Examples).
[0123] (Assembly of electrolytic capacitors)
[0124] The wound body having the solid electrolyte formed therein was immersed in the liquid component shown in Table 3 for 5 minutes in a reduced pressure atmosphere (40 kPa). Thus, a capacitor element impregnated with the liquid component was obtained. The obtained capacitor element was sealed to complete Figure 1 Then, an aging treatment was performed at 130°C for 2 hours while applying the rated voltage.
[0125] [Evaluation 2]
[0126] (Measurement of electrostatic capacitance and ESR)
[0127] The electrolytic capacitors obtained were measured for capacitance and initial ESR. In addition, in order to evaluate long-term reliability, the ESR increase rate (ΔESR) was confirmed while the rated voltage was applied and the capacitors were kept at 145°C for 2000 hours. ΔESR was expressed as the ratio (Z / Z0) of the ESR (Z) after being kept at 145°C to the initial value (Z0).
[0128] The evaluation results are shown in Table 4. Table 4 also shows the change in pH (YX) obtained in the same manner as in Evaluation 1 for each liquid component.
[0129] Table 3
[0130]
[0131] [Table 4]
[0132]
[0133] 《Electrolytic capacitors CA7~CA10 and CB5~CB8》
[0134] Except that the polymer dispersion and the solid electrolyte were not prepared, an electrolytic capacitor was produced in the same manner as the electrolytic capacitors CA1 to CA4 and CB1 to CB4 and subjected to aging treatment. Evaluation 2 was performed using the obtained electrolytic capacitor.
[0135] The evaluation results are shown in Table 5. Table 5 also shows the change in pH of each liquid component (YX).
[0136] [Table 5]
[0137]
[0138] Although the present invention has been described with respect to the current preferred embodiments, such disclosure is not to be construed restrictively. For those skilled in the art in the technical field of the present invention, various modifications and changes will undoubtedly be apparent upon reading the above disclosure. Therefore, the appended claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present invention.
[0139] Industrial Applicability
[0140] The liquid component of the present application is useful in an aluminum electrolytic capacitor or an electrolytic capacitor including a conductive polymer and a liquid component.
[0141] Description of Reference Numerals
[0142] 10: capacitor element, 11: bottom housing, 12: sealing member, 13: seat plate, 14A, 14B: lead wires, 15A, 15B: lead wire connectors, 21: anode body, 22: cathode body, 23: spacer, 24: anti-roll tape
Claims
1. A liquid component for an electrolytic capacitor, comprising a central atom and a ligand, wherein the central atom is at least one selected from boron, aluminum and silicon, and the ligand has a plurality of coordination atoms bonded to the central atom, The liquid component further comprises at least one cation selected from a cation comprising a nitrogen atom and a cation comprising a phosphorus atom, The coordinating atom is at least one selected from oxygen and nitrogen, and is bonded to a carbon atom having no oxo group, The central atom forms a complex anion with the ligand, The ratio of the complex anion in the electrolyte salt containing the complex anion and the cation is 15 mass % or more and 90 mass % or less. 2 . The liquid component for electrolytic capacitors according to claim 1 , wherein an increase in pH when the liquid component is kept at a temperature of 145° C. for 1000 hours is 3 or less.
3. The liquid component for electrolytic capacitor according to claim 1, wherein The molar ratio of the cation to the complex anion (=complex anion / cation) is 0.9 or more and 1.1 or less.
4. The liquid component for electrolytic capacitor according to any one of claims 1 to 3, wherein The cation includes at least one selected from secondary ammonium ions, tertiary ammonium ions, and quaternary ammonium ions.
5. The liquid component for electrolytic capacitor according to any one of claims 1 to 3, wherein The cation comprises a quaternary ammonium ion.
6. The liquid component for electrolytic capacitor according to any one of claims 1 to 3, wherein The content of the complex anion is 0.1 mass % or more and 30 mass % or less.
7. The liquid component for electrolytic capacitor according to any one of claims 1 to 3, wherein The amount of water contained in the liquid component is 0.1 to 30% by mass or less.
8. The liquid component for electrolytic capacitor according to any one of claims 1 to 3, wherein The ligand is derived from a polyol having an aromatic ring and at least a first hydroxyl group and a second hydroxyl group, The first hydroxyl group is bonded to the aromatic ring, The group containing the second hydroxyl group is bonded to the ortho position of the first hydroxyl group, The group including the second hydroxyl group is the second hydroxyl group or an alkyl group having 1 to 4 carbon atoms and having the second hydroxyl group.
9. The liquid component for electrolytic capacitor according to claim 8, wherein Each central atom is coordinated with two or three ligands. 10 . The liquid component for electrolytic capacitor according to claim 1 , further comprising a polymer polyether solvent.
11. The liquid component for electrolytic capacitor according to any one of claims 1 to 3 and 9, wherein The ligand includes a substituent having electron withdrawing property.
12. An electrolytic capacitor comprising: An anode body having a dielectric layer formed on the surface, cathode body, and A conductive polymer disposed between the anode body and the cathode body, and the liquid component according to any one of claims 1 to 11.
13. The electrolytic capacitor according to claim 12, wherein: The conductive polymer is doped with a dopant.
14. The electrolytic capacitor according to claim 13, wherein: The dopant includes a polymer anion.
15. An electrolytic capacitor comprising: An anode body having a dielectric layer formed on the surface, cathode body, and The liquid component according to any one of claims 1 to 11 disposed between the anode body and the cathode body.
16. The electrolytic capacitor according to any one of claims 12 to 15, wherein: The liquid component has a pH of 6 or less.
